Women empowerment as a determinant of investments in children in selected rural communities in Nigeria (2013)
The study established the influence of women empowerment on investments in children in selected rural communities in Nigeria. A total of two hundred and fifty rural women from Ile-lfe and its environs constituted the sample for the study. Their ages ranged from 15years to 39years with a mean age of 26.7years and standard deviation of 7.08. The two instruments used were author-constructed interview guide questionnaires with 0.69 and 0.74 reliability coefficient respectively. The data obtained were analyzed using Frequency counts, percentages, chi-square, and multiple regression statistics. The results obtained from the study indicated that, a combination of the six independent variables significantly predicted the dependent variable. The result also indicated that, significant relationship existed between each of the variables and children schooling, health and survival. Based on the results of these findings, it was recommended that those in the helping professions should take cognizance of those variables that have been found to influence investing in children schooling, health and survival. The result also recommended intervention strategy to help families, couples and the individuals for modifying attitudes and behavior on gender issues.